Serial I-123-FP-CIT SPECT Image Findings of Parkinson's Disease Patients With Levodopa-Induced Dyskinesia - Jeong, Eun Hye; Sunwoo, Mun Kyung; Song, Yoo Sung (Frontiers in Neurology, 2018)
Background: Levodopa-induced dyskinesia (LID) is a major complication of dopamine replacement drug usage in parkinson's disease (PD) patients. Since the mechanism of LID is yet unclear, we analyzed serial [I-123] N-ω-fluoropropyl- 2β-carbomethoxy- 3β-(4-iodophenyl) nortropane (I-123 FP-CIT) single photon emission computed tomography (SPECT) images. We investigated the changes of dopaminergic innervation during the progression of PD in relation to the development of LID. Methods: Data were obtained from the Parkinson's Progression Markers Initiative (PPMI) database. 290 PD dopamine replacement drug-naïve patients (age 61.0 ± 9.7, M: F = 195: 95) were enrolled. I-123 FP-CIT SPECT images from baseline, 12 months, 24 months, and 48 months were analyzed among with clinical factors. Specific binding ratios (SBRs) of the striatal regions from I-123 FP-CIT SPECT images were analyzed. We used independent tests and logistic regression for analysis of LID risk association. Results: Among 290 patients, 36 patients developed LID after 48 months follow-up. Baseline MDS-UPDRS Part II and III scores were significantly higher in the PD patients with LID, compared with the PD patients without LID. Striatal SBRs were significantly lower in the PD patients without LID at baseline, 24 months, and 48 months (p < 0.001). Multivariate analysis revealed MDS-UPDRS Part II and putaminal SBRs at baseline and 24 months to be significantly associated with the development of LID (p < 0.001). Also, patients who developed LID at 48 months had a higher decrease rate of putaminal SBR at the 24 months (p < 0.05, and 48 months (p < 0.01) period. Conclusion: In this study, we demonstrated the serial changes of nigrostriatal dopaminergic innervation in relationship to LID development for the first time. The deterioration rate of dopaminergic innervation was significantly higher in the PD patients who developed LID, compared with the PD patients who did not develop LID. Serial follow up I-123 FP-CIT SPECT acquisition during the course of PD could be helpful in predicting the development of LID.